1995
DOI: 10.1002/cne.903560308
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic localization of opioid receptors in vocal control regions of a male passerine bird (Junco hyemalis)

Abstract: Previous studies have found opioid peptide-like immunoreactivity in avian vocal control regions, but whether these regions contain receptors for opioid peptides has not been examined. To address this question, we used quantitative in vitro autoradiography to determine the anatomical distribution and to measure the densities of mu, delta, and kappa opioid receptors in vocal control regions (area X, higher vocal center, and nucleus intercollicularis) of adult male dark-eyed juncos (Junco hyemalis). To evaluate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 91 publications
5
27
1
Order By: Relevance
“…A qRT-PCR analysis demonstrated that there were no significant differences in m-OR mRNA expression between HVC and PNP, and the expression of d-OR mRNA was uniformly lower than m-OR mRNA expression in these regions. Our findings were similar to those of Gulledge and Deviche (1995) who demonstrated that the expression of m-ORs was greater than that of d-ORs in HVC in juncos. Whereas HVC of adult male juncos expressed low levels of d-ORs and this nucleus appeared as a clear area within the surrounding PNP, the expression of m-ORs was uniform throughout PNP, inclusive of HVC (Gulledge and Deviche, 1999).…”
Section: Opioid Receptor Expression In Brain Regions Involved In Vocasupporting
confidence: 94%
See 2 more Smart Citations
“…A qRT-PCR analysis demonstrated that there were no significant differences in m-OR mRNA expression between HVC and PNP, and the expression of d-OR mRNA was uniformly lower than m-OR mRNA expression in these regions. Our findings were similar to those of Gulledge and Deviche (1995) who demonstrated that the expression of m-ORs was greater than that of d-ORs in HVC in juncos. Whereas HVC of adult male juncos expressed low levels of d-ORs and this nucleus appeared as a clear area within the surrounding PNP, the expression of m-ORs was uniform throughout PNP, inclusive of HVC (Gulledge and Deviche, 1999).…”
Section: Opioid Receptor Expression In Brain Regions Involved In Vocasupporting
confidence: 94%
“…That is, Area X expresses higher levels of m-OR mRNA compared to MSt in adult and juvenile juncos of both sexes, but not in adult male zebra finches, the reasons for which are unclear. Although Gulledge and Deviche (1995) had suggested that these differences in OR expression were unlikely to be linked to singing since the densities of m-ORs in Area X did not vary seasonally in male juncos, recent evidence suggests otherwise. Wada et al (2006) have shown that proenkephalin (the peptide precursor of enkephalin) is upregulated in the processes of Area X (and HVC) neurons during singing in adult male zebra finches.…”
Section: Or Mrna Expression and Localization Of Opioid Receptors In Cmentioning
confidence: 92%
See 1 more Smart Citation
“…Males continue to sing during the summer breeding season but rarely thereafter, when they prepare to migrate south. A previous study identified opioid receptors in brain regions of the junco song system including the HVC, RA, and Area X, which control song learning and production, and found no seasonal differences in receptor densities (Gulledge and Deviche, 1995). Given the involvement of VTA and POM opioid receptors in motivation or reward, we hypothesized that birds express opioid receptors in these regions and receptors would be present at higher densities during than outside the breeding season.…”
Section: Introductionmentioning
confidence: 98%
“…Administration of T, or its metabolite E 2 , increases neuronal number and size in HVC and Area X in song sparrows, white-crowned sparrows (Zonotrichia leucophrys gambelii), and darkeyed juncos (Junco hyemalis), and increases neuron size in RA (Gulledge & Deviche, 1995;Tramontin et al, 2003;Soma et al, 2004). The arborization of neurons within RA is profoundly affected by E 2 in the adult canary, with the number of dendrites and synaptic profiles increasing with steroid administration (DeVoogd & Nottebohm, 1981).…”
Section: Seasonal Adult Neuroplasticity In the Song Systemmentioning
confidence: 99%